A Molecular Barium Hydrido Complex Stabilized by a Super‐Bulky Hydrotris(pyrazolyl)borate Ligand. (5th December 2017) - Shi, Xianghui; Hou, Cuiping; Zhou, Chulu; Song, Yanyao; Cheng, Jianhua
Abstract: Hydrogenolysis of the scorpionate‐supported barium alkyl complex (Tp Ad, iPr )Ba[CH(SiMe3 )2 ](THF) (Tp Ad, iPr =hydrotris(3‐adamantyl‐5‐isopropyl‐pyrazolyl)borate) afforded the dinuclear barium hydrido complex [(Tp Ad, iPr )Ba(μ‐H)]2 (2 ), which was characterized by NMR spectroscopy and single‐crystal X‐ray analysis. Exposure of2 with 1 atm of CO resulted in a reductive coupling process to form the cis‐ethendiolate dianion (3 ). Reaction of2 with one equivalent of PhC≡C−C≡CPh gave barium 1, 4‐diphenyl‐2‐butyne‐1, 4‐diyl complex {[(Tp Ad, iPr )Ba]2 (PhCH−C≡C−CHPh) (4 ).